Peran Interaksi Simbolik dalam Membuat Content Marketing untuk Menciptakan Brand Engagement Media Sosial @dailysocial.id - Febridianti, Dayang Gasani Aqila; Pribadi, Muhammad Adi (Prologia, 2023)
Along with the development of internet media, social media has also developed into various types. The most popular social media in Indonesia is Instagram. On Instagram there are various kinds of content, one of which is in the field of marketing which is usually used for content marketing. Content marketing is made to market and introduce products provided by a company. DailySocial.id utilizes content marketing for potential customers and regular customers. The content marketing process requires brand engagement to measure the interest of potential consumers towards DailySocial.id products, the process is explained through symbolic interaction theory. This study discusses the role of symbolic interaction in the creation of content marketing to create brand engagement on the DailySocial.id Instagram account. This study uses the theory from Mead which discusses symbolic interaction, content marketing by Kee and Yazdanifard and brand engagement which is discussed by Saraswati and Hastari. The research method used by the researcher is a case study with a qualitative exploratory approach. Informants in this study were marketing staff and followers of Instagram accounts from DailySocial.id. Informants were chosen because they have been adapted to the needs of the author to meet the data. There are two types of data used, namely primary data obtained by observation, in-depth interviews, as well as documentation and secondary data in the form of archival records and literature studies. The data that has been obtained must go through the process of data processing, presentation, drawing conclusions and the validity of the data in the form of adequacy of references, checking members, and detailed descriptions. The results of the study indicate that the process of creating content marketing carried out by DailySocial.id has shown success in creating brand engagement. Seiring perkembangan media internet, media sosial juga ikut berkembang menjadi beragam jenisnya. Media sosial yang paling diminati oleh masyarakat Indonesia adalah Instagram. Di Instagram terdapat berbagai macam konten, salah satunya di bidang pemasaran yang biasanya digunakan untuk content marketing. Content marketing dibuat untuk memasarkan dan memperkenalkan produk-produk yang disediakan oleh suatu perusahaan. DailySocial.id memanfaatkan content marketing untuk para calon pelanggan dan pelanggan tetap. Proses content marketing membutuhkan brand engagement untuk mengukur ketertarikan calon konsumen terhadap produk DailySocial.id, prosesnya dijabarkan melalui teori interaksi simbolik. Penelitian ini membahas bagaimana peran interaksi simbolik dalam pembuatan content marketing untuk menciptakan brand engagement di akun Instagram DailySocial.id. Penelitian ini menggunakan teori dari Mead yang membahas tentang interaksi simbolik, content marketing oleh Kee dan Yazdanifard dan brand engagement yang dibahas oleh Saraswati dan Hastari. Metode penelitian yang digunakan oleh peneliti adalah studi kasus dengan pendekatan eksploratif kualitatif. Informan pada penelitian ini adalah staf marketing dan pengikut akun instagram dari DailySocial.id. Informan dipilih karena sudah disesuaikan dengan kebutuhan penulis untuk memenuhi data. Ada dua jenis data yang digunakan yaitu data primer yang diperoleh dengan observasi, wawancara mendalam, serta dokumentasi dan data sekunder yang berupa rekaman arsip dan studi pustaka. Data yang sudah diperoleh harus melalui proses pengolahan data, penyajian, menarik kesimpulan serta keabsahan data berupa kecukupan referensi, pengecekan anggota, dan uraian rinci. Hasil penelitian menunjukkan bahwa dalam proses pembuatan content marketing yang dilakukan oleh DailySocial.id telah menunjukkan adanya keberhasilan dalam menciptakan brand engagement.